Model Pendukung Keputusan Berbasis Analitical Hierarchy Process Dalam Pemenuhan Alat Keselamatan Kapal Motor Tradisional - Prakoso, Muhammad Ravi; Pratomo, Sunu Arsy; Diansisti, Anisa (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
Traditional wooden motorboats are ships that are built traditionally based on the experience of the builder without a basic design process like modern ships. The sizes of traditional wooden ships are usually small and are mostly used as fishing vessels, passenger ships and inter-island cargo ships, especially in eastern Indonesia. Traditional wooden motor boats have become a means of local transportation to serve shipping needs in the regions and as a means of local transportation. Sailing certainly has various problems which can be caused by weather factors, the condition of shipping lanes, other ships, and things beyond human capabilities, which can cause shipping disruptions and even cause emergencies. Emergency means a situation outside normal conditions that occurs on board a ship which has a tendency to endanger human life, property, objects and the environment where the ship is located. One way to anticipate emergency events is to provide safety equipment. IMO (International Marine Organization) as a maritime world organization issued SOLAS (Safety of Life at Sea) which contains provisions regarding what safety equipment is on board ships such as Life Jackets, Ring Buoys and Fire Extinguisher. However, in fact, fulfilling the safety equipment requires independent costs from traditional motorboat owners so there is a priority in fulfilling the safety equipment. Based on the results of the Analytical Hierarchy Process calculations in priority fulfillment of safety equipment with the final result of 36.6% Life Jacket, 30.8% Ring Buoy and 33.6% Fire Extinguisher. With these results, ship owners can determine their priorities in anticipating future emergencies